2022
DOI: 10.18805/lr-4811
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate and Association Studies in Short Duration Pigeonpea [Cajanus cajan (L.) Millsp.] Genotypes

Abstract: Background: Absolute understanding of the relationship between yield and yield attributing traits contributing to variance is predominant in a breeding programme. To study the multivariate analysis and interrelationship among the yield and yield attributing traits in the pigeonpea, 68 genotypes were subjected to principal component analysis and association studies. Methods: The 68 pigeonpea genotypes were raised during two seasons viz., rabi, 2019-2020 and rabi, 2020-2021 in a randomized complete block design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…The minimum diversity was contributed by pods/plant (2.38%) followed by primary branches/plant (4.76%), days to 50% flowering (6.19%) and plant height (8.10%). This is in conformity with Naing et al [12] when they reported that more contribution towards genetic diversity for pigeon pea are days to maturity, pods/plant, days to 50% flowering and seed yield; Ranjani et al [8] observed that maximum contribution towards the genetic diversity for the traits i.e., 100-seed weight and days to maturity; Sandeep et al [14] reported maximum contribution for seed yield, 100-seed weight and days to 50% flowering [15].…”
Section: Clusters Mean and Percentage Contribution For Different Trai...supporting
confidence: 90%
See 1 more Smart Citation
“…The minimum diversity was contributed by pods/plant (2.38%) followed by primary branches/plant (4.76%), days to 50% flowering (6.19%) and plant height (8.10%). This is in conformity with Naing et al [12] when they reported that more contribution towards genetic diversity for pigeon pea are days to maturity, pods/plant, days to 50% flowering and seed yield; Ranjani et al [8] observed that maximum contribution towards the genetic diversity for the traits i.e., 100-seed weight and days to maturity; Sandeep et al [14] reported maximum contribution for seed yield, 100-seed weight and days to 50% flowering [15].…”
Section: Clusters Mean and Percentage Contribution For Different Trai...supporting
confidence: 90%
“…These all genotypes were grouped into six clusters by using Toucher's method based on eight quantitatively inherited characters which represent the vast genetic diversity and it could be used for further crop improvement programmes. Similar results were also reported by previous researcher i.e., Ranjani et al [8] and Sharma et al [9] observed seven and nine cluster groups from 68 genotypes, respectively; Kandarkar et al [10] showed that the twentyseven genotypes were grouped into six clusters. The present investigated results revealed that among the six clusters highest number of genotypes were included in cluster I (16) whereas all the other five clusters comprised of one genotype per cluster (Table 2).…”
Section: Genetic Diversitysupporting
confidence: 90%
“…The difference in magnitude between Genetic Coefficient of Variation (GCV) and Phenotypic Coefficient of Variation (PCV) was minimal for all traits, indicating a reduced influence of environmental factors on trait expression. Several studies, including those conducted by Ranjani et al (2021) [8] , have reported minimal variation between GCV and PCV for various characteristics in pigeonpea. According to Burton (1952), this suggests that the observed variability in the traits is predominantly due to genetic factors rather than environmental influences.…”
Section: Resultsmentioning
confidence: 93%